2013
DOI: 10.1097/brs.0b013e31826c63cb
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Massive Blood Loss in Scoliosis Surgery From Preoperative Variables

Abstract: Risk of massive blood loss (total blood loss > 30% of estimated blood volume) in patients with scoliosis could increase, if they (1) had preoperative Cobb angle larger than 50º or (2) planned to undergo osteotomy or fusion of more than 6 levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0
14

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 18 publications
5
71
0
14
Order By: Relevance
“…A greater number of levels instrumented and increased operative time likely indicate a more complex procedure that could be associated with a greater number of postoperative issues, such as pain management and prolonged rehabilitation. A greater number of levels fused also has been associated with increased blood loss and thus, need for a blood transfusion, which could prolong LOS [11,17,54]. There may be a benefit to reducing operative blood loss in order to reduce postoperative LOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A greater number of levels instrumented and increased operative time likely indicate a more complex procedure that could be associated with a greater number of postoperative issues, such as pain management and prolonged rehabilitation. A greater number of levels fused also has been associated with increased blood loss and thus, need for a blood transfusion, which could prolong LOS [11,17,54]. There may be a benefit to reducing operative blood loss in order to reduce postoperative LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Such factors are not only important clinically and for setting appropriate patient expectations, but they also are closely tied to total hospital costs associated with the procedure [30]. The information we have on risk factors for AEs in patients undergoing PSF have been derived mainly from studies that either were limited by small sample size [21,41,44,54], only studied one variable [2,16,25,29,31,42,44,45,50,55], included patients with neuromuscular scoliosis and cerebral palsy [5,19,20,24,32,43], used potentially flawed administratively coded or self-reported data [5,7,35,51], or included adult patients with deformity [35].…”
Section: Introductionmentioning
confidence: 99%
“…These may be patient factors such as gender, skeletal maturity, Cobb angle, kyphosis, activated partial thromboplastin time level and fibrinogen level, and menstruation cycle phase [15][16][17][18][19] or surgery-related, number of fusion level, operative time, stages of surgery, number of osteotomies, and surgical approach. 2,15,17,[19][20][21][22][23] Some of the above factors such as number of vertebral levels fused, number of screws inserted, duration of surgery, and Cobb angle demonstrated positive correlation with total blood loss in our study. Recently, a dual surgeon approach was also reported to result in shorter operative time, less blood loss, and lower risk of allogenic blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…These systematic protocols bring together various risk management strategies that are designed to target specific complications individually [16,[36][37][38]. Joy et al found that the implementation of a standardized handover protocol significantly reduced the number of technical errors and information omissions that occurred when patients were transitioned from the operating room to intensive care.…”
Section: Comprehensive Standardized Perioperative Protocolsmentioning
confidence: 99%
“…Short-term complications include local or systemic infection, thromboembolism, poor wound healing, implant-related problems with neurologic sequelae, postoperative pain requiring reoperation, and complications arising from comorbid conditions. Long-term complications include pseudarthrosis, latent infection, implant fatigue and failure, and proximal and distal junctional failures [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%